Structural-Stability Relationship in a Series of [ZnX]\(^-\) Inorganic Organic Hybrid Materials (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2018)
To scrutinize the role the weak interactions in structure-stability of [ZnX]- (X = Cl, Br, I) based derivatives, three series of inorganic-organic hybrid materials were studied through single crystal X-ray crystallographic data obtained from IUCr in CIF format. The organic constituent of the hybrid compounds is holding the inorganic moiety through D-H...X interactions, where D is N, C or O of organic moiety acts as H-donor atom and X of inorganic component is Cl, Br I or F behaves as H-acceptor atom.  The structural parameters such as the Zn-X bond distance lies in the range of 2.019(5) í…  [ZnF-3] to 2.730(4) í… [ZnCl-1] and X-Zn-X bond angle has minimum value of 82.35o and maximum value of 180o for [ZnF-3], were calculated. The maximum twist of X-Zn...Zn-X = 179.8(3)o at symmetry position of 0.5+x, 0.5-y, 0.5+z is observed in [ZnBr-7] derivative.
Keywords: Non-covalent interactions; Structure stability; Hg motifs; Mercurophilic interactions and 1D-2D structural parameters